Viral protein R inhibitors from Swertia chirata of Myanmar - Woo, So-Yeun; Win, Nwet Nwet; Noe Oo, Wyine Myat; Ngwe, Hla; Ito, Takuya; Abe, Ikuro; Morita, Hiroyuki (Journal of bioscience and bioengineering, 2019)
Viral protein R (Vpr) is a small, basic accessory protein (14 kDa) that is well conserved in Human immunodeficiency virus-1 (HIV-1), HIV-2, and simian immunodeficiency virus (SIV). Numerous investigations over the past 2 decades have suggested that Vpr would be an attractive target for HIV disease treatment. Small molecules, including fumagillin, damnacanthal, quercetin, vipirinin, isopimarane diterpenoids, picrasane quassinoids, iridoids, and bis-iridoid glycosides, have been reported as potent Vpr inhibitors. These compounds may not only represent HIV drug seeds, but also could be new target compounds for biochemical synthesis such as current synthetic biology and enzyme bioengineering approaches, due to their anti-Vpr activities. In our investigations of different types of compounds with Vpr inhibitory activity, we found that the CHCl3 soluble, crude extract of the whole Swertia chirata plant inhibited the expression of Vpr in Hela cells harboring the TREx plasmid encoding full-length Vpr (TREx-HeLa-Vpr cells). The purification and isolation of the active CHCl3 soluble portion afforded six secondary metabolites, including four xanthone derivatives, decussatine (1), methylswertianin (2), 1-hydroxy-3,5-dimethoxyxanthone (3), and bellidifolin (4), and two triterpenoids, oleanolic acid (5) and 12-hydroxyoleanolic lactone (6). The evaluation of the anti-Vpr activities of 1, 2, and 4−6 against TREx-HeLa-Vpr cells revealed that 4 and 5 are potent Vpr inhibitors with an effective dose of 10 μM, and are chemically and structurally distinct from previously reported inhibitors. [Display omitted]